Open Government and Open Government Implementations: An Evaluation of Public Institutions in Turkey - Şahika EROĞLU (Ankara Üniversitesi Dil ve Tarih-Coğrafya Fakültesi Dergisi, 2018)
Open Government is defined in the literature as a way of providing use/re-use and the publication of governmental data in open formats via open platforms in order to obtain economical, social and political benefits. Recently, many countries have attempted to provide more efficient processes related to transparency, accountability by opening their public data. This study aims to analyze current conditions of public institutions involved in open government process in Turkey. In this regard, 21 Turkish institutions which are involved in the existing e-government platform and which are responsible for the open government applications are analyzed via an assessment tool developed in the shade of the literature review and existing models. The results of our analysis reflect that there are insufficiencies in terms of political/administrative infrastructures in Turkish institutions. In line with the results, recommendations related to identified problems were offered at the end of the study.